Utilizing ChatGPT within the Cybergogy Model to Optimize Self-Directed Learning in the Instructional Multimedia Course at PTIK - Ashadi, Ninik Rahayu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to identify how ChatGPT, as an artificial intelligence technology, is utilized to support students’ self-directed learning in the Instructional Multimedia course. The research employed a descriptive quantitative approach, which systematically and factually describes the phenomenon of ChatGPT utilization within the Cybergogy model to support self-directed learning among PTIK students in the Multimedia Learning course. The population in the class serving as the research subject consisted of 32 students. Based on the results, viewed from several aspects: Engagement (Digital Involvement) shows that ChatGPT is highly helpful in understanding Multimedia Learning materials (mean 4.55) and increases learning motivation due to quick access to explanations and examples. In the aspect of Empowerment (Self-Directed Learning Empowerment), ChatGPT is very effective in generating ideas and inspiration for multimedia design (mean 4.48) and helps students complete tasks independently while still ensuring personal understanding. In the Enhancement (Improvement and Reflection) aspect, ChatGPT enhances the depth of understanding regarding multimedia design principles. In the aspect of Ethical & Critical Use, students are aware of using ChatGPT as a support tool rather than a substitute for their own thinking.The study concludes that the utilization of ChatGPT within the Cybergogy Model effectively optimizes self-directed learning in the Instructional Multimedia course at PTIK, viewed through four aspects: (1) Engagement, (2) Empowerment, (3) Enhancement, and (4) Ethical & Critical Use. The overall mean score obtained was 4.316, with the majority category being very high.